The Batik Motif Design Development Through the Transformation of the Mahligai Temple, Muara Takus Temple in Kampar District - Sarwani, Roni; Budiwirman, Budiwirman (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
Roni Sarwani, 2022. Transformation of the Mahligai Stupa ofMuara Takus Temple as a Batik Motif Design in KamparRegency. Thesis proposal. Padang State University PostgraduateProgram.Based on the existing conditions, it is known that the root of theproblem in the field of Malay batik product design in the form ofBatik Motif Design Development through the Transformation ofthe Mahligai Stupa of Muara Takus Temple in Kampar Regency,is due to a lack of human resources who have the potential to becreative and innovative in creating batik motif designs bytransforming the Stupa Mahligai Muara Takus Temple inKampar Regency. So that this condition resulted in the quality ofcommunity resources to be low. To improve the quality ofcommunity resources in Kampar Regency, efforts have beenmade to develop regionally distinctive batik motif designs. Thegoal to be achieved in the development of this batik motif designis the preservation of Malay culture in the transformation ofcultural objects as a typical batik motif design for the KamparRegency area.The type of this research is Batik Motif Design DevelopmentResearch developed using four-D models. Data collection wascarried out by validating and testing the developed product. Thedesign will be designed, validated by experts, to determine thepracticality and effectiveness of the motif designs developed.Batik motif designs were produced through the transformation ofthe Mahligai Stupa of Muara Takus Temple in Kampar Regencyas a valid effort to preserve local culture. Based on the pre-testconducted in the batik motif design process, it is known that itsimplementation is in the very practical category. The responsefrom the local community is urgently needed in thetransformation of the batik motif design of the Mahligai Stupa ofMuara Takus Temple into a batik motif design in KamparRegency which is developed into positive results. Pre-observationresults showed good results. In addition, this research alsoproduced two training products in the form of 1) Batik MotifDesign Development Book, 2) batik products in the form of batikcloth.Keywords: Design of Batik Motifs, Transformation of theMahligai Stupa of Muara Takus Temple, Batik in KamparRegency